PERAN ECPAT DALAM MENANGANI CSEC OLEH WISATAWAN ASING DI THAILAND - Lestari, Eka Mulyani; Wiranata, S,IP., M.A, I Made Anom; Resen, S.IP., M.A, Putu Titah Kawitri (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2015)
ABSTRACK This study is aimed at describing ECPAT’s role and strategies to prevent and eliminate CSEC by foreign tourists in Thailand. Tourism in Thailand has given the negative impact, which is CSEC by foreign tourists in Thailand. ECPAT, as the NGO that has visions and missions to combat CSEC, then seeks to eliminate all forms of CSEC in Thailand.This study describes the role of ECPAT to eliminates CSEC by foreign tourists in Thailand and which strategies used by ECPAT to prevent and eliminates CSEC by foreign tourists in Thailand. This research has found ECPAT as an organisation has certain roles as an agenda setter, educator and also counterpart in order to eliminates CSEC by foreign tourists in Thailand. This study used qualitative methodelogy and examined by using Civil Society Organisations and Transnationalism as concepts and theory within 2005 to 2012 as timeline. Keyword: ECPAT, Thailand, CSEC, child sexual tourists